Pengaruh Media Sosial terhadap Kreativitas Remaja di Karang Taruna Griya Manunggal Sejahtera II Kauman Kidul Salatiga - Dwi Aji Saputra; Yari Dwikurnaningsih; Sapto Irawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the significance of the influence of social media on youth creativity in Karang Taruna Griya Manunggal Sejahtera II Kauman Kidul Salatiga. This type of research is comparative causal to determine the effect of the independent variable (X) social media on the dependent variable (Y) creativity. The population in this study were 46 teenagers from Karang Taruna Giya Manunggal Sejahtera II, while the samples were taken using total sampling technique. Data collection techniques in this study used a scale and the results were analyzed using a simple linear regression technique with the help of the SPSS 25.0 program. The results of this study indicate that there is a significant influence between social media on the creativity of adolescents in Karang Taruna Griya Manunggal Sejahtera II Kauman Kidul Salatiga. This is evidenced by the acquisition of a tcount value greater than ttable, namely 7.206 greater than 2.015 (7.206 > 2.015) and a Sig. of 0.000 < 0.05 (p = 0.000 < 0.05). In addition, this study also obtained an R Square value or a coefficient of determination of 0.541, which means that social media contributes 54.1% to the creativity of Karang Taruna youth and the remaining 45.9% is influenced by other variables not examined.